Optimizing Student Activities Through BOS Funds in Improving Learning Achievement (Case Study of SMA Negeri 7 Bandung) - H. Soro , Suharyanto; Sari Fatimah, Retno Intan; Utami, Intan Puji (Global Education Journal, 2025)
This study examines the optimization of student activities through the use of BOS funds and their impact on student achievement at SMA Negeri 7 Bandung. BOS funds, which since 2005 have become an important instrument in equalizing and improving the quality of education, have not been fully utilized optimally for the development of student activities. Meanwhile, these activities play an important role in shaping character and supporting student achievement. This study aims to analyze the planning, implementation, supervision, and evaluation of student activities based on the use of BOS funds, as well as their contribution to students' academic and non-academic achievements. This study uses a case study approach with a qualitative paradigm. Data collection methods use observation, interviews, and documentation studies. The samples or respondents in this study include the principal, teachers, supervisors, and students. Data analysis was carried out using the Miles and Huberman interactive model, and data validity was maintained through triangulation and member checking. The results of the study indicate that (1) The use of BOS funds for student activities at SMA Negeri 7 Bandung is carried out in a planned, participatory, and transparent manner; (2). The funds are used to support OSIS programs, extracurricular activities, training, and academic and non-academic competitions; (3) This optimization has a positive impact on improving student achievement, both academically and in character, and creating a collaborative and achievement-oriented school climate. The conclusion of this study is that the use of BOS funds at SMA Negeri 7 Kota Bandung is effective in supporting student activities that are oriented towards improving achievement and character building.